2002
DOI: 10.1007/s00439-002-0780-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a gene influencing heart rate on chromosome 4 among hypertensives

Abstract: While mechanisms are poorly understood, resting heart rate has been shown to be a strong predictor of the risk of cardiovascular disease, cancer, and all-cause mortality. We performed a genome scan for quantitative trait loci influencing the resting heart rate among 962 Caucasians and 1,124 African-Americans in the Hypertension Genetic Epidemiology Network (HyperGEN), a multi-center study of genetic and environmental factors related to hypertension. The NHLBI Mammalian Genotyping Service typed a total of 391 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
1
24
2
Order By: Relevance
“…In the race specific models of heart rate the characteristics with the largest effects on heart rate were hypertension status, beta blocker use and gender. Beta-blocker medication was significantly associated with a lower resting heart rate among hypertensives, but other hypertensive medications were not strongly related to resting heart rate, which is consistent with our prior report for this cohort (Wilk et al 2002) and the findings of Ranade et al (2002). Since hypertension status and beta blocker use may be effect modifiers of the association between AR polymorphisms and heart rate, we controlled for these factors in analysis by stratification.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the race specific models of heart rate the characteristics with the largest effects on heart rate were hypertension status, beta blocker use and gender. Beta-blocker medication was significantly associated with a lower resting heart rate among hypertensives, but other hypertensive medications were not strongly related to resting heart rate, which is consistent with our prior report for this cohort (Wilk et al 2002) and the findings of Ranade et al (2002). Since hypertension status and beta blocker use may be effect modifiers of the association between AR polymorphisms and heart rate, we controlled for these factors in analysis by stratification.…”
Section: Resultssupporting
confidence: 88%
“…The mean value of six heart rate measures was the dependant variable in a GEE model with all four SNPs and covariates. The covariates included in the model were the same as those used previously to create an adjusted phenotype for genome-wide linkage analyses (Wilk et al 2002), which included age, BMI, sex, alcohol drinking, current smoking, former smoking, blocks walked per day, and hours of TV watched per weekday.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A genome scan for resting heart rate in 513 African Americans from the Hypergen study found a peak at this same location on chromosome 3 (124 cM) for resting heart rate, after adjusting for a series of covariates including BMI (LOD 1.35). 32 Evidence suggests that increased sympathetic nervous system activity, measured by a resting heart rate, is related to aspects of insulin resistance syndrome. 33,34 A linkage analysis for adiponectin in Pima Indians, not treated pharmacologically for diabetes, demonstrated a peak (LOD ¼ 1.8-1.9) at the same location (124 cM) with and without adjusting for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that the main finding of the 41 genome scan for resting heart rate is a linkage peak in both Caucasians and African Americans at 195 cM located on chromosome 4.…”
Section: Discussionmentioning
confidence: 99%